Surfactant proteins levels in asthmatic patients and their correlation with severity of asthma: a systematic review - Sagad O.O. Mohamed; Amged Mohammed; Tarteel Mohamed; Hanaa Fadil; Mohamed S.K. Salih; Amna H. Mohamed; Alrumaisa Alhassan; Safaa G. A. Saeed; Fatima S.K. Salih; Huda M. A. Mustafa; Somaia M.M. Ahmed; Esraa M. A. Garalnabi; et al. (BMC Pulmonary Medicine)
Abstract Background Surfactant decreases surface tension in the peripheral airways and plays a role in regulating the lung’s immune responses. Several reports have documented changes in surfactant proteins levels, especially surfactant protein D (SP-D) and surfactant protein A (SP-A), suggesting their potential as biomarkers for asthma. However, the results of these studies are controversial. This systematic review was done to assess the levels of surfactant proteins in asthmatic patients compared to healthy individuals. Methods A systematic review was conducted according to PRISMA guidelines. Searches were performed in the Medline/PubMed, Web of Science, Embase, and ScienceDirect databases to identify studies that assessed surfactants proteins levels in asthmatic patients. Pooled standardized mean differences (SMDs) with 95% confidence intervals (CIs) were calculated using R version 4.4.3 meta package. Results A total of 16 studies met the inclusion criteria and were thus considered for this systematic review. Among these, SP-D was the most frequently studied protein in relation to asthma, asthma severity, and lung function parameters in asthmatic patients. Serum and sputum levels of SP-D in asthmatic patients were slightly elevated compared to non-asthmatic individuals. However, these differences were not statistically significant; the pooled SMDs were 0.27 (95% CI: -0.034 to 0.574, P = 0.082) for serum levels and 1.47 (95% CI, -0.197 to 3.103, P = 0.084) for sputum levels. Similarly, no significant difference was detected for the analysis of serum SP-A levels, with SMD = 0.18 (95% CI, -0.505 to 0.866, P = 0.606). Though, some of the reviewed studies showed an association between SP-D levels and disease severity in asthmatic patients. Conclusion Although alterations have been observed in asthma and proposed as biomarkers, this systematic review did not find significant differences in the levels between asthmatics and healthy individuals. However, some studies have suggested an association between SP-D levels and asthma severity. Given the limited number of studies investigating this association, further research is needed to validate the clinical relevance of correlation between SP-D levels and asthma severity.